422 Impact of COVID-19 on injury-related emergency department visits in North Carolina, USA. (20th November 2022) - Waller, Anna; Harmon, Katherine; Proescholdbell, Scott; Marshall, Stephen
Abstract : Background: The global COVID-19 pandemic impacted population-level emergency department (ED) utilization patterns for treatment of acute injuries. We examined the frequency and proportion of North Carolina, USA (NC) ED visits for injury during the first two years of the COVID-19 pandemic. Methods: Data for the years 2019–2021 were obtained from NC DETECT, NC's statewide syndromic surveillance system. Frequencies and proportions of injury-related ED visits overall and for selected injury mechanisms were compared, along with counts and proportions of COVID-Like-Illness (CLI) ED visits. Results: As compared to 2019 (N=924, 663), the total number of injury-related ED visits declined in 2020 (N=748, 427) and 2021 (N=766, 794). As a proportion of total ED visits, injury-related ED visits decreased only slightly from 2019–2021 (18.7% to 17.8%). Most injury mechanisms saw a decrease in the number of ED visits in 2020 with a partial rebound in numbers in 2021. Drug overdoses, however, increased each year, with a total 14.9% increase from 2019 to 2021; the proportion of overdose visits to all ED visits only increased in 2020. Firearm injury spiked alarmingly in 2020 then fell somewhat in 2021. Early in the pandemic, injury-related ED visits decreased sharply as CLI ED visits increased. While CLI visits remained high, injury-related visits rebounded but generally did not return to pre-pandemic levels. Conclusion: Both ED avoidance and decreased exposures may have contributed to declines, while increases in select injury mechanisms may reflect unanticipated impacts of COVID-19 mitigation strategies. Learning Outcomes: Injury outcomes exacerbated by the pandemic require timely public health responses.